2016
DOI: 10.1016/j.ajic.2016.04.251
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of methicillin-resistant Staphylococcus aureus infection in long-term care is possible while maintaining patient socialization: A prospective randomized clinical trial

Abstract: On-site MRSA surveillance with targeted decolonization resulted in a significant decrease in clinical MRSA infection among LTCF residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…Patients with these risk factors should be appropriate targets for interventions. MDRO colonization increases the risk of MDRO infection [4-6, 15, 16], but is typically amenable to interventions [28][29][30][31][32][33][34]. Current standard interventions for MDRO reduction (eg, curbing antibiotic use and discontinuing indwelling devices) and patients' improving health status throughout the post-acute care stay have been thought to be sufficient reasons to presume that MDROs would decolonize by the time of discharge to the community.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with these risk factors should be appropriate targets for interventions. MDRO colonization increases the risk of MDRO infection [4-6, 15, 16], but is typically amenable to interventions [28][29][30][31][32][33][34]. Current standard interventions for MDRO reduction (eg, curbing antibiotic use and discontinuing indwelling devices) and patients' improving health status throughout the post-acute care stay have been thought to be sufficient reasons to presume that MDROs would decolonize by the time of discharge to the community.…”
Section: Discussionmentioning
confidence: 99%
“…Three systematic reviews and 3 studies (2 experimental, 1 quasi-experimental) found evidence that chlorhexidine bathing reduces MRSA acquisition and carriage, although one review did include studies where no reduction was found. 7 , 11 , 12 , 14 , 15 , 17 A prospective cohort study by Ruiz et al 16 (2017) found no reduction in MRSA colonization rates but did find a significant reduction in total MDRO colonization.…”
Section: Resultsmentioning
confidence: 99%
“…If one develops a targeted admission surveillance program based on risk factors for C. difficile colonization, which we have done for our system-wide surveillance implementation, one will likely test 1/3 of admissions (our practice) thereby reducing the cost to an effective level. Also, based on the performance of the test we used, the expectation is that there will be one unnecessary isolated patient per 200 admissions [21], which we consider an acceptable number resulting from a false positive test result. Finally, one could argue that our use of a NAAT for routine clinical diagnostic testing could result in an over estimation of the burden of HO-CDI at our organization [41].…”
Section: Plos Onementioning
confidence: 99%
“…Since large studies have demonstrated that AST at admission can lower MRSA clinical disease rates [18], it would be expected that C. difficile could respond to similar practice, with resulting lower CDI rates [19]. We had previously demonstrated the benefit of admission MRSA AST on lowering clinical infection [20,21], and our hypothesis was that this approach also would be successful for CDI. Thus, the goal of our pragmatic, stepped-wedge infection control initiative was to determine if admission AST for toxigenic C. difficile would lead to a reduced hospital onset CDI (HO-CDI) incidence at our healthcare organization.…”
Section: Introductionmentioning
confidence: 97%